P13 Major depressive disorder in patients with wilson's disease: relationship with liver disease, neurological disease and quality of life. (28th September 2020) - Camarata, Michelle; Ala, Aftab; Maciejewski, Kaitlin; To, Uyen; Zimbrean, Paula; Rubman, Susan; Patel, Amar; Wadhwa, Anant; Coskun, Ayse; Apdik, Tugce; Tomlin, Ricarda; Deng, Yanhong; et al.
Abstract : Introduction: Mental health problems are underappreciated in Wilson disease (WD) (Schaefer et al. 2016). We aimed to determine: i) the prevalence and clinical features of major depressive disorder (MDD) in adults with WD ii) whether MDD correlates with liver and neurological disease and quality of life (QOL). Method: A multi-site international WD registry was developed and initiated in December 2017. At enrolment adults (n=55) were evaluated using questionnaires and administered exams assessing cognition, mood, psychosis, substance use, anxiety, perceived stress, personality change and QOL. MDD was determined using the investigator led MINI-7 questionnaire. Patients also underwent hepatology and neurological assessments (UWDRS). We reviewed patient reported depression at first presentation and diagnosis. Statistical analysis using SAS9.4 (SAS Institute; Cary, NC) included summary statistics, Wilcoxon Rank Sum test and categorical comparisons using Chi-squared or Fisher's exact test. Results: Depression was reported in 26% at first presentation of WD (33% at diagnosis). At enrolment 35% had a lifetime history of MDD. At evaluation 5 patients with lifetime MDD took antidepressants; 1 without. At enrolment 36.33% were suffering from symptoms of current depression based on the PHQ-9 (self-administered). Cirrhosis was present in 24% based on imaging, APRI and Fib4 scores. There was no association between cirrhosis and depression symptomology (PHQ-9 score >9). In those with depression symptomology, 1 had cirrhosis and 6 did not. Liver disease severity did not differ in cirrhotics with MDD and those without (median Child-Pugh 5 (5–9) vs. 5 (5–9), p=0.13). Two patients (1 with MDD) took medication for hepatic encephalopathy. No significant difference in neurological total UWDRS scores was found in those with MDD vs. without (median 8 (0–73) vs. 4 (0–40), p=0.22). A neurological UWDRS total score >0 was not associated with lifetime MDD status (79% vs. 81%, p=1.00). Patients with MDD had worse mental health QOL (median 43 vs. 52.7 p=0.042), more suicidal ideation (32% vs. 8%, p=0.05), higher anxiety (p=0.008), higher perceived stress (median 19 vs. 9, p=0.007), and more neuroticism (median 7 vs. 4.5, p=0.006). We found no significant difference in physical health QOL in MDD (median 55.6 vs. 56.3, p=0.69). Conclusion: MDD is highly prevalent in WD and associated with worse mental health QOL. The risk appears higher than other liver diseases (Lee et al. 2013. Psychosomatics, 4:52–9). We did not find an association between the severity of liver, neurological disease and MDD. Screening for depression should be considered in patients with WD.